2013
DOI: 10.15376/biores.8.1.923-932
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Bundle Corrugated Laminated Composites (BCLC). Part II. Damage Analysis under Low Velocity Impact Loading

Abstract: The objective of this study was to investigate the deformation behavior and damage model of bamboo bundle corrugated laminated composites under low velocity impact loading. The influence of different stacking sequences, i.e., bamboo bundle parallel to the corrugated waves (type I), cross-ply (type II), and perpendicular to the waves (type III), in laminates was studied in regard to impact loading. A shape parameter, K, was developed to quantify the effect of corrugation on impact response. The results of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Among them, the most serious and complex is the impact loading, as invisible damage of various kinds occurs easily in the composites [3,4]. These failures, including matrix cracking, interfacial debonding, fiber breakage, and delamination, have a deleterious effect on the mechanical and physical properties of the composites [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the most serious and complex is the impact loading, as invisible damage of various kinds occurs easily in the composites [3,4]. These failures, including matrix cracking, interfacial debonding, fiber breakage, and delamination, have a deleterious effect on the mechanical and physical properties of the composites [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [10] studied the low-velocity impact properties and damage mechanisms for bamboo scrimber and bamboo/wood scrimbers with different densities and concluded that bamboo scrimber with higher density showed better impact performance. Jiang et al [7] investigated the impact properties of bamboo bundle corrugated laminated composites with three stacking sequences and found that the effect of the corrugated shape on the impact properties of composites was positive for bamboo bundles parallel to the corrugated waves, but negative for cross-ply board. However, the curing state of adhesion for the board made with preprocessing densification technology was completely different from the analysis above.…”
Section: Introductionmentioning
confidence: 99%
“…One of these forms includes an interesting arrangement of two layers of corrugation in close proximity, so that frictional contact between the layers dissipates yet further impact energy. Jiang et al [73] considered impact on corrugations made from bamboo fibre based composites. This paper finds that the laminate stacking sequence and corrugation direction have a complicated effect on the impact energy absorbed by the impact, with a unidirectional layup with fibres oriented along the corrugation channels being optimal.…”
Section: -4 Impactmentioning
confidence: 99%
“…Bamboo bundle laminated veneer lumber (BLVL) is a bamboo-based composite developed as a promising material for engineering applications because of advantages such as good dimensional stability, excellent mechanical performance, and a high resource yield ratio (over 90%) (Chen et al 2013a;Jiang et al 2013). Additionally, the methods used to study the changes in mechanical performance during the aging resistance test on bamboo-based products were adopted in previous works (Tomak et al 2012;Yu et al 2013;Huang a et al 2014) Recently, an intermittent hot-pressing process has been developed and applied to produce BLVLs with lengths greater than 6 m (Chen et al 2013b).…”
Section: Introductionmentioning
confidence: 99%